Freirean reflections and continuing education in health in the regulation center for the access to health care (Research, Society and Development, 2022)
The aim of this study is to reflect in the light of Paulo Freire on the possibility of connecting care practice in a Regulation Center with Permanent Education in order to contribute to improving access to SUS services. It is a Theoretical reflection with a qualitative approach, anchored in the political precepts of Permanent Education in Health and in the light of Paulo Freire. By systematizing educational ideals that propose reflective construction based on an action-reflection process, the necessary problematization is obtained to explore a network that analyzes the work process carried out in the work context of the Regulation Centers. The permanent educational strategy materializes and drives the generation of knowledge by directing actions and transformations of reality in meaningful learning environments based on dialogicity between peers. with the reality arising from the fragmented care model to which the daily life of Brazilian health services is part, we find in the Freiriana philosophy, the motivation to rethink about the importance of its practice to the detriment of the problematization of sensitive points and thus produce strategies of action towards collaborative and horizontal construction among the actors of this process in the search for a dignified, fair and equitable health.